Traumatic bilateral ureteral tear in a pregnant woman after a motor vehicle crash: a case report. Issue 9 (30th September 2020) - Abu-Rmaileh, Muhammad; Jensen, Hanna; Kimbrough, Mary Katherine
Abstract: Bilateral ureteropelvic junction (UPJ) tears are rare. Trauma can obscure this diagnosis. The objective of this case report is to highlight the rapid diagnosis of this injury and care in the case of pregnancy. A 22-year-old pregnant female was ejected from her car and presented with abdominal pain. The patient got a computed tomography (CT)-chest, abdomen, pelvis (CT-CAP) revealing bilateral ureteral injury, which was confirmed on retrograde cystoscopy. Her injuries were treated with nephrostomy tubes with plans for definitive repair after pregnancy. Fetus remained stable throughout her care and the patient was discharged with no complications. Due to the rapid diagnosis and effective stabilization, the patient and fetus recovered well from the injuries and multiple procedures. While there are many explanations for bilateral UPJ tears, deceleration and hyperextension seem to be the two major mechanisms of this injury.